Developpemnt Du Capital Humain, Croissance Economique Et Bien-Etre En Côte d’Ivoire - Koné, Seydou (European Scientific Journal, ESJ, 2016)
This paper assesses human capital development policies and their impact on economic growth and households’ well-being in Côte d'Ivoire. A dynamic computable general equilibrium model was used to measure the impact of public spending on education and health policies as predicted by the government and then the effects of a larger increase of those spending on economic growth and household welfare in Côte d'Ivoire. The simulations results show that public spending in education and health has positive impacts on education and health demands, on the improvement of labor’s factor quality and on the productive capacities of poor and vulnerable households. The results also show that there is a positive correlation between public expenditures on education and health, economic growth and welfare in Côte d'Ivoire.